Risk of non‐AIDS‐defining events among HIV‐infected patients not yet on antiretroviral therapy1. Issue 5 (21st January 2015) - Zhang, S; van Sighem, A; Kesselring, A; Gras, L; Prins, JM; Hassink, E; Kauffmann, R; Richter, C; de Wolf, F; Reiss, P; ATHENA national observational HIV cohort study
<x xml:space="preserve">Abstract</x> Objectives Certain non‐AIDS‐related diseases have been associated with immunodeficiency and HIV RNA levels in HIV‐infected patients on combination antiretroviral therapy (cART). We aimed to investigate these associations in patients not yet on cART, when potential antiretroviral‐drug‐related effects are absent and variation in RNA levels is greater. Methods Associations between, on the one hand, time‐updated CD4 counts and plasma HIV RNA and, on the other hand, a composite non‐AIDS‐related endpoint, including major cardiovascular diseases, liver fibrosis/cirrhosis, and non‐AIDS‐related malignancies, were studied with multivariate Poisson regression models in 12 800 patients diagnosed with HIV infection from 1998 onwards while not yet treated with cART. Results During 18 646 person‐years of follow‐up, 203 non‐AIDS‐related events occurred. Compared with a CD4 count ≥ 500 cells/μL, adjusted relative risks (RRs) for the composite endpoint were 4.71 [95% confidence interval (CI) 2.98‐7.45] for a CD4 count < 200 cells/μL, 2.06 (95% CI 1.38–3.06) for a CD4 count of 200–349 cells/μL, and 1.19 (95% CI 0.82–1.74) for a CD4 count of 350–499 cells/μL. There was no evidence for an independent association with HIV RNA. Other important covariates were age [RR 1.40 (95% CI 1.31–1.49) per 5 years older], hepatitis B virus coinfection [RR 5.66 (95% CI 3.87–8.28)] and hepatitis C virus coinfection [RR 9.26 (95% CI 6.04–14.2)]. Conclusions In persons not yet receiving cART, a more severe degree of immunodeficiency rather than higher HIV RNA levels appears to be associated with an increased risk of our composite non‐AIDS‐related endpoint. Larger studies are needed to address these associations for individual non‐AIDS‐related events.